Instrumen Hukum Penegakan Hak Asasi Manusia di Indonesia - Sri Warjiyati (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2018)
The issue of human rights today is not only a national problem as well as a global problem. The existence of human rights embodies various forms of influencing the existence of basic obligations, in which both constitute a unity that cannot be separated and run in parallel. Basically, the nature and nature of human rights are the same, but the implementation and enforcement of human rights in each country will never seem to be the same. Human rights enforcement in Indonesia is currently faced with a number of significant problems. One of them is the decline of Indonesia's state legal system and the decline of other systems that also influence such as political, economic and social systems. For example in the economic field, the condition of Indonesian society is generally in the poverty line, not a few of the people commit violations of human rights for economic reasons. In this case the settlement method offered in the issue of human rights enforcement in Indonesia is pursued through the reconstruction of the national legal system in Indonesia by restructuring law enforcement institutions. Thus, it is expected that the national legal system will be reorganized and will significantly influence the improvement of other systems including the enforcement of human rights.Permasalahan tentang hak asasi manusia saat ini tidak hanya menjadi masalah nasional sekaligus masalah global. Adanya hak asasi manusia mewujudkan berbagai bentuk pengaruh adanya kewajiban asasi, di mana keduanya merupakan satu kesatuan yang tak dapat dipisahkan dan berjalan secara paralel. Penegakan HAM di Indonesia saat ini dihadapkan dengan berbagai masalah yang cukup signifikan. Misalnya di bidang ekonomi, kondisi masyarakat indonesia pada umumnya berada dalam garis kemiskinan, tidak sedikit sebagian masyarakat melakukan pelanggaran terhadap HAM karena alasan ekonomi. Dalam hal ini cara penyelesaian yang di tawarkan dalam permasalahan penegakan HAM di Indonesia adalah dengan diupayakan melalui rekonstruksi sistem hukum nasional di Indonesia dengan melakukan restrukturisasi institusi-institusi penegakan hukum. Dengan demikian, diharapkan sistem hukum nasional dapat ditata kembali serta berpengaruh secara signifikan terhadap perbaikan sistem dalam penegakan HAM.